2016
DOI: 10.1002/dvg.22931
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans Q neuroblasts: A powerful system to study cell migration at single‐cell resolution in vivo

Abstract: Summary: During development, cell migration plays a central role in the formation of tissues and organs. Understanding the molecular mechanisms that drive and control these migrations is a key challenge in developmental biology that will provide important insights into disease processes, including cancer cell metastasis. In this article, we discuss the Caenorhabditis elegans Q neuroblasts and their descendants as a tool to study cell migration at single-cell resolution in vivo. The highly stereotypical migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Loss of PRY-1 function mimics constitutively active WNT pathways with high MAB-5 expression in the QR cell and their progeny, resulting in their migration in an opposite (posterior) direction [120] (Figure 5A,B). Genetic studies have identified other components of the WNT pathway including the ligand, EGL-20, as well as BAR-1 [126] ( Figure 5B). Other neuronal processes in which roles for pry-1 have been demonstrated include axon guidance and synapse formation.…”
Section: Neuronal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of PRY-1 function mimics constitutively active WNT pathways with high MAB-5 expression in the QR cell and their progeny, resulting in their migration in an opposite (posterior) direction [120] (Figure 5A,B). Genetic studies have identified other components of the WNT pathway including the ligand, EGL-20, as well as BAR-1 [126] ( Figure 5B). Other neuronal processes in which roles for pry-1 have been demonstrated include axon guidance and synapse formation.…”
Section: Neuronal Developmentmentioning
confidence: 99%
“…Other neuronal processes in which roles for pry-1 have been demonstrated include axon guidance and synapse formation. Axonal function was uncovered in a genetic screen using an RNAi Molecular genetic studies have shown that pry-1-mediated WNT signaling is essential for the migration of Q-lineage cells and guiding them along specific trajectories [126]. PRY-1 activity is specifically needed in the QR cell to restrict mab-5 (male abnormal 5)/Hox (homeobox) expression and to enable anterior migration of their descendants.…”
Section: Neuronal Developmentmentioning
confidence: 99%
“…Finally, the daughter cells of QR.pa, called QR.paa and QR.pap (hereafter called QR.pax), acquire a neuronal identity (Chalfie and Sulston, 1981;White et al, 1986). Much is known about the signaling pathways, transcription factors and cytoskeleton regulating their posterior-toanterior direction and orientation of migration (Middelkoop and Korswagen, 2014;Josephson et al, 2016;Rella et al, 2016). Concerning the termination of migration and final cell positioning, the posterior-to-anterior QR.pa lineage stops upon expression of the Wnt receptor MIG-1 (Mentink et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, preventing QR migration or increasing its speed does not alter the timing of mig-1 expression (Mentink et al, 2014). After QR.pa stops migrating, its daughter cells QR.pax separate in a dorso-ventral direction while crossing each other in an anteroposterior direction (Rella et al, 2016;Altun and Hall, 2020); they then differentiate without further change in cell body position ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Much information concerning mechanisms underlying cell migration in C. elegans has emerged from the study of a few major motile events. Some of these have recently been reviewed elsewhere, including ventral enclosure (Vuong-Brender et al 2016), Q neuroblast migration (Rella et al 2016) and axon guidance (Chisholm et al 2016). Our review focuses on what has been learned and promising future studies on three distinct cellular movements that are common motility modes in animals: anchor cell (AC) invasion as a model for invasion through basement membrane (BM) barriers; distal tip cell (DTC) migration as a model for how a BMencased leader cell directs organ formation; and sex myoblast (SM) migration as a model for how cells migrate between tissues.…”
mentioning
confidence: 99%